Sustainability, competitive advantage, and innovation in manufacturing industry in Mexicali, Baja California, Mexico (GEON Journal (Management, Organizations and Business), 2026)
Problem statement. The epistemic community points out that economic, environmental, and social sustainability are closely related to competitive advantage and innovation; however, it is unclear what set of activities should be developed to achieve them. Objectives. To determine the relationship between economic, environmental, and social sustainability, competitive advantage, and innovation. Materials and methods. The research is cross-sectional and uses quantitative methods to test six research hypotheses. Results. Economic, social, and environmental sustainability, as well as competitive advantage and innovation, exhibit a low-to-moderate positive relationship. Discussion. Companies that embrace innovation are more likely to gain sustainable competitive advantages. Conclusions. Economic, social, and environmental sustainability, as well as competitive advantage and innovation, are topics essential for any organization. Contribution/originality. The study was conducted in manufacturing companies in the city of Mexicali, Baja California, Mexico.
Keywords: Environment; Innovation; Economic competitiveness; Business management